Plane and solid mensuration : worktext - Mateo, Rhea R.; Bataclan, Napoleon A.;Bunag, Edwin S. (Quezon City, Philippines : C & E Publishing Inc., 2013)
Mensuration is the process of measuring the lengths of lines, areas of surfaces, and volumes of solids using algebraic equations and geometric calculation. Mensuration may be divided into two parts-plane mensuration and solid mesuration.
Chapter 1. Basic mathematical concepts -- Chapter 2. Perimeter, circumference and areas of different plane figures -- Chapter 3. Prisms and Cylinders -- Chapter 4. Pyramids and Cones -- Chapter 5. Frustums, Prismatoids, and Truncated Solids -- Chapter 6. Spheres.
Includes bibliographical references.
Keywords: PLANE -- MENSURATION -- FIGURES